EVALUASI PENERAPAN STANDAR OPERASIONAL PROSEDUR KARYAWAN PANEN TERHADAP KUALITAS DAN KUANTITAS PANEN TANDAN BUAH SEGAR KELAPA SAWIT (Elaels guineensis jacq) SERTA HANCAK PANEN (Studi Kasus: PT. Sentosa Kalimantan Jaya) - Lydia Apria Rosadi; Rusli Anwar; Rusmini (JURNAL AGRIMENT, 2020)
This research is motivated by the number of oil palm companies that require employees to do work according to standards companies such as harvest employees who must harvest according to quality ripe fruit and harvest ripe reach the company's target, but in the statement the harvest work does not pay attention to operational standards procedures (SOP) that have been made and implemented in the company, so it is necessary carried out observations of the application of standard operating procedures for employees to harvest fresh fruit bunches (FFB). The objectives of this research are to identify the characteristics of respondents based on age, sex, work experience, education in general and to monitor the implementation of standard operating procedures for harvest employees on the quality and quantity of harvested fresh oil palm fruit bunches and harvest rights.Collecting data related to the implementation of harvest employee SOPs was obtained through the observation method, the interview method, and the documentation method.To analyze this data, data analysis was used in this study collected from research sources using descriptive analysis methods and Likert scale.